NMDA Receptor Function During Senescence: Implication on Cognitive Performance - Kumar, Ashok (Frontiers in Neuroscience, 2015)
N-methyl-D-aspartate (NMDA) receptors, a family of L-glutamate receptors, play an important role in learning and memory, and are critical for spatial memory. These receptors are tetrameric ion channels composed of a family of related subunits. One of the hallmarks of the aging human population is a decline in cognitive function; studies in the past couple of years have demonstrated deterioration in NMDA receptor subunit expression and function with advancing age. However, a direct relationship between impaired memory function and a decline in NMDA receptors is still ambiguous. Recent studies indicate a link between an age-associated NMDA receptor hypofunction and memory impairment and provide evidence that age-associated enhanced oxidative stress might be contributing to the alterations associated with senescence. However, clear evidence is still deficient in demonstrating the underlying mechanisms and a relationship between age-associated impaired cognitive faculties and NMDA receptor hypofunction. The current review intends to present an overview of the research findings regarding changes in expression of various NMDA receptor subunits and deficits in NMDA receptor function during senescence and its implication in age-associated impaired hippocampal-dependent memory function.